ANALISA LAPORAN KEUANGAN MENGGUNAKAN RASIO LIKUIDITAS PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) BMT AL-ITTIHAD RUMBAI TAHUN 2019-2021 - Ningsih, Nadia Yulisma; Menhard, Menhard; Sari, Maya Rizki (Politeknik Negeri Ambon, 2023)
This study aims to see how the liquidity of the BMT Al-Ittihad Savings and Loans and Sharia Financing Cooperative (KSPPS) BMT Al-Ittihad is viewed from the Liquidity Ratio. This research was conducted at the BMT Al-Ittihad Rumbai Savings and Loans Cooperative and Sharia Financing (KSPPS) which is located at Komplek Damar No. 610 Camp PT. CPI, Rumbai Pekanbaru City. The research object used is the financial statements of KSPPS BMT Al-Ittihad, namely the Financial Position Report from 2019 to 2021. This research data was obtained through observation. The method of data analysis used in this study is a descriptive method, namely a method that is carried out by collecting, processing, presenting and analyzing data so that a detailed picture of the research is obtained. The results of the study show that 1) The Liquidity of KSPPS BMT Al-Ittihad in 2019-2021 seen from the Current Ratio is said to be not good because the Current Ratio percentage value is below the industry average standard of 200% or Current Ratio <200%. In 2019 the percentage value is 124%, in 2020 it is 112% and in 2021 it is 114%. 2) The liquidity of KSPPS BMT Al-Ittihad in 2019-2021, seen from the Quick Ratio, is said to be not good because the Quick Ratio percentage value is below the industry average standard of 150% or Quick Ratio <150%. In 2019 the percentage value is 122%, in 2020 it is 112% and in 2021 it is 114%. 3) The Liquidity of KSPPS BMT Al-Ittihad in 2019-2021 seen from the Cash Ratio is said to be not good because the Cash Ratio percentage value is below the industry average standard of 50% or Cash Ratio <50%. In 2019 the percentage value is 33.8%, in 2020 it is 8.89% and in 2021 it is 13.9%.